PRKDC regulates cGAMP to enhance immune response in lung cancer treatment - Huang, Zhanghao; Huang, Runqi; Zhu, Jun; Zhou, Youlang; Shi, Jiahai (Frontiers in Immunology, 2024)
BackgroundDespite its involvement in nucleotide metabolism, tumor immune landscape, and immunotherapy response, the role of 2’-3’-cyclic guanosine monophosphate–adenosine monophosphate (2’,3’-cGAMP) in lung adenocarcinoma (LUAD) remails unelucidated. This study aimed to investigate the antitumor effects of 2’,3’-cGAMP in LUAD.MethodHerein, patients with LUAD were screened for prognostic biomarkers, which were then assessed for sensitivity to immunotherapy and chemotherapy utilizing the “TIDE” algorithm and CellMiner database. The results were validated using a mouse xenograft model. Additionally, macrophages and lung cancer cells were co-cultured, and macrophage polarization and apoptosis levels in the lung cancer cells were detected through flow cytometry. Protein levels were analyzed through western blotting and immunofluorescence. Finally, drug-encapsulated nanoparticles were designed to systematically examine the antitumor efficacy of the treatment against LUAD.ResultNotably, 2’,3’-cGAMP-mediated protein kinase, DNA-activated, catalytic subunit (PRKDC) inhibition induced macrophage polarization toward the M1 phenotype, thereby triggering apoptosis in LUAD cells. Furthermore, in vivo experiments showed that M1 macrophage infiltration enhancement and apoptosis induction in lung cancer cells were achieved by suppressing PRKDC expression via 2’,3’-cGAMP, which inhibited lung cancer growth. The machine-learning approaches revealed SB505124 to be an effective antitumor agent in LUAD cells with high PRKDC levels owing to its ability to promote 2’,3’-cGAMP-mediated apoptosis. Encapsulation of 2’,3’-cGAMP, and SB505124 within a nano-delivery system markedly reduced tumor volumes in murine lung cancer tissues compared with that by individual agents.ConclusionThe findings of this study reveal that PRKDC can predict poor survival of patients with LUAD. Additionally, SB505124 enhances the efficacy of 2’,3’-cGAMP-based immunotherapy in patients exhibiting a high PRKDC expression.